ANALYSIS OF HOSPITAL MORBIDITY FOR PANCREATIC CANCER IN KRASNOYARSK KRAI - Е. V. Okladnikova; Т. G. Ruksha (Сибирский онкологический журнал)
Characteristics of hospital morbidity for pancreatic cancer among the population of Krasnoyarsky Krai between 2009 and 2013 were studied. The majority of patients (82.16 %) were diagnosed with advanced pancreatic cancer, with the incidence peak at 51–60 years and approximately equal male to female ratio. The main risk factors were overweight (in 67.66 % of patients) and diabetes (in 21.99 % of patients). The role of hereditary predisposition to the development of pancreatic cancer was not established.